Effects of Pamelo Orange Peel (Citrus maxima) Ethanol Extract on Macroscopic Kidney and Heart of Hypertensive Rats: Efek Ekstrak Etanol Kulit Jeruk Pamelo (Citrus maxima) pada Makroskopik Ginjal dan Jantung Tikus Hipertensi - Arifin, Sukmawati; Emelda, Andi; Santi, Irma; Putrisari, Nur Awaliah; Intan, Tri Rahmaputri Nur; Husain, Nurul Fadillah; Adawiyah, Rabiyah Al (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Background: Hypertension, characterized by elevated blood pressure (â‰¥140/90 mmHg), leads to kidney and heart damage. Hypertension causes increased heart rate, heart enlargement, risk of heart failure, and damage to kidney blood vessels. One way to treat hypertension is by administering drugs such as herbal medicines. Pamelo oranges (Citrus maxima) are starting to be developed in the treatment of diseases. The ethanol extract of pomelo orange peel (EEKJP) contains flavonoid compounds which have antihypertensive activity as a natural Angiotensin Converting Enzyme (ACE) inhibitor, diuretic, increases Nitric Oxide Synthase (NOS) activity and activates Endothelium Derived Relaxing Factor (EDRF). Objectives: This study aims to examine the effect of ethanol extract of pomelo orange peel on the macroscopic features of the heart and kidneys of hypertensive rats (Rattus norvegicus). Methods: This research uses The Posttest-Only Control Group Design. Thirty rats were divided into six groups, namely naive control, negative control (NaCMC 1%), positive control (Captopril 0,45 mg/200 gramBB), EEKJP 100 mg/KgBW group, EEKJP 150 mg/KgBW group, and EEKJP 200 mg/KgBW group. Hypertension condition through induction with prednisone 1.5 mg/KgBW and NaCl 2% for 21th days. The test preparation was administered orally for 14th days. Next, all rats were dissected to remove the heart and kidney organs for macroscopic observations. Results: The results of the study showed that ethanol extract of pomelo (Citrus maxima) orange peel had a varied effect on the macroscopic appearance of the heart and kidneys of rats with hypertension. The heart organ shows structural improvements, while the kidneys have not shown any improvement. Conclusions: Extract with a dose of 100 mg/KgBW has no changes in the macroscopic appearance of the heart so it is thought to be able to repair damage to the heart organ.